Особливості формування асортимнету наукоємної продукціїї в Україні - Полякова, Анастасія Ігорівна (НТУ "ХПІ", 2018)
Розглянуті особливості та проблеми ринку наукомісткої продукції в Україні, стан науково-технологічного потенціалу, фінансове забезпечення наукової та науково-технічної діяльності, динаміка наукоємності внутрішнього валового продукту, а також особливості функціонування національного ринку товарів високих технологій. Окреслено роль наукоємної продукції у розвитку національної економіки. Досліджено основні відмінні риси наукоємної продукції та визначено їх основні характеристики з широкого кола показників з метою виявлення специфічних особливостей, які впливають на формування асортименту наукоємної продукції. Аналізуються система формування асортименту наукоємної продукції та вплив особливостей наукоємної продукції на її формування.

The features and problems of the market of science-intensive products in Ukraine, the state of scientific and technological potential, the financial support of scientific and technological activities, the dynamics of a high-tech domestic gross product, as well as the functioning of the national market for high-technology goods were reviewed. The role of science-intensive products in the development of the national economy has been determined. The main distinctive features of science-intensive products are studied and their main characteristics are determined by a wide range of indicators in order to identify specific features that influence the formation of an assortment of science-intensive products. The system of formation of assortment of the high technology production and influence of features of the high technology production on its formation are analyzed.
Features of formation of assortment by scientific production in Ukraine
Keywords: науково-дослідна робота; дослідно-конструкторська робота; науково-технічна сфера; фінансове забезпечення; ринок; high technology products; assortment formation